182k views
5 votes
(4h+6h2 +1) – (5h2– 8h4 +6)
Need help simplify

User ErikE
by
6.0k points

2 Answers

1 vote

Answer:

8h^4+h^2+4h-5

Explanation:

(4h+6h^2+1)-(5h^2-8h^4+6)

4h+6h^2+1-5h^2+8h^4-6

8h^4+h^2+4h+1-6

8h^4+h^2+4h-5

User Calvillo
by
6.6k points
3 votes

Explanation:

4h+6h2+1−(5h2−8h4+6)

=4h+6h2+1+−1(5h2−8h4+6)

=4h+6h2+1+−1(5h2)+−1(−8h4)+(−1)(6)

=4h+6h2+1+−5h2+8h4+−6

=4h+6h2+1+−5h2+8h4+−6

=(8h4)+(6h2+−5h2)+(4h)+(1+−6)

=8h4+h2+4h+−5 <- Answer

hope this helps <3

User Jeffrey Vaughan
by
5.7k points